Correction: Wide-angle lasing from photonic crystal nanostructures of a liquid-crystalline blue phase. Issue 35 (29th August 2019) - Zhuo, Guan-Yu; Huang, Shu-Wei; Lin, Chi-Huang; Lin, Shih-Hung
Abstract : Correction for 'Wide-angle lasing from photonic crystal nanostructures of a liquid-crystalline blue phase' by Guan-Yu Zhuo et al., J. Mater. Chem. C, 2019, 7, 6433–6439.